MODEL KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN KERJA GURU DI SMK POLIMEDIK KOTA DEPOK - Khasnah Syaidah; Muhammad Latif (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2022)
This study examines the situational leadership model of the principal in improving the work discipline of teachers at the Polymedic Vocational School of Depok City. This study uses a qualitative method with a description approach. Methods of data collection using interview techniques, documentation, and observation. Data analysis uses data reduction, data presentation, and drawing conclusions. The situational leadership model of the principal applied at the Polymedicine Vocational School of Depok City shows that there are four leadership styles. First, telling or instructions; Second, selling or consulting; Third, participating or participatory; Fourth, delegating or delegation. This study found that the principal at the Polymedic Vocational School in Depok City was more dominant in using the participatory leadership style and the delegation leadership style, while the instructional and consulting leadership style was only applied to teachers who still needed more comprehensive guidance and direction. The principal at the Depok City Polymedicine Vocational School uses a situational leadership style that is applied by looking at the readiness and maturity of the teachers to carry out the work given by the principal. This readiness and maturity is obtained from the level of direction and guidance given by the principal and the emotional support provided by the principal to his teachers. The formation of readiness and maturity in teachers is able to have implications for an increase in work discipline. This study concludes that the situational leadership of the principal at the Polymedic Vocational School in Depok City is based on the interaction of the principal and teacher which focuses on emotional maturity, so that with the emotional maturity level of the teacher gives birth to high work discipline. Discipline is an attitude or behavior that describes compliance with a rule and provision for the sake of an orderly, orderly and comfortable life in accordance with the goals to be achieved